TINJAUAN HUKUM ISLAM DALAM PRAKTIK BAGI HASIL BUDIDAYA UDANG VANAME GAMPONG UJONG BLANG KECAMATAN BANDA SAKTI - Yunus, Muhammad; Cut Ali, Isnu (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2022)
The researcher wants to research about field research. This research also uses qualitative research methods. The method that will be used by researchers in this study is a method to get a description of the problems that occur in the field and their conclusions. The results of the research conducted by this researcher can be concluded that the profit sharing in the Vaname shrimp cultivation business in Ujung Blang Village, Banda Sakti District begins with the expansion of the cages, the purchase of seeds, to maintenance, capital from the owner of the capital itself. While the manager or cultivator is obliged to develop and maintain as well as with the procedures for managing the entire implementation of cultivation until the harvest period. The results are divided between the owners of the capital to get a profit of 85% while the tenants get a profit of 15% of the net proceeds. If there is a loss, the tenant does not get the profit sharing. This is in accordance with the provisions of the Mudharabah contract which states that business losses and damage to goods in the Mudharabah agreement that are experienced not due to negligence of the mudharib or implementer will be borne by the owner of the capital. The development of the Vaname shrimp farming business was initially only 75,000 individuals to be managed by the tenants. Then the owner of the capital invites his partner to work together to manage his cultivation. And currently the number of Vaname shrimp seeds in the culture weighs about 1.5 tons with a total of 75,000 tails.